Does latest match outcome influence subsequent mental training demands and mental fatigue? A longitudinal study in youth-elite soccer - Rubio-Morales, A.; Díaz-García, J.; Russell, S.; López-Gajardo, M. Á.; Ponce-Bordón, J. C.; García-Calvo, T. (International Journal of Sport and Exercise Psychology, 2026)
This study explored the effects of previous match outcomes on subsequent mental effort, training-related mental fatigue, and player wellness scores. 26 youth-elite soccer players (Mage = 17.5 ± 1.2y) participated across a full-season. Mental load and wellness were assessed using Likert scale questionnaires. Mental fatigue was quantified by a 100 mm Visual Analogue Scale. Data were collected at 4 training occasions/week (Monday = MD+1, Wednesday = MD-4, Thursday = MD-3 and Saturday = MD-1), across 38 weeks with a competitive match on Sunday. A Linear Mixed Model was run, using training days and the previous match outcome as fixed effects. No significant effects of the previous match outcome were found on mental effort or mental fatigue for any subsequent training day (p > .05). MD-4 and MD-3 were identified as the most mentally demanding trainings, with MD+1 reported as the most mentally fatiguing. With regard wellness score, it was observed that a negative (i.e., draw or loss) match outcome significantly increased the stress (p < .05) and worsened the mood state (p < .001) reported on MD+1. In conclusion, coaches are recommended to manipulate task constraints and utilise load, taper and recovery strategies to counter perceived mental fatigue during the competitive week and the effects of match outcomes on players` wellness.